The Effect of Using Canva Media on Descriptive Text Writing Ability of Seventh Grade Students - Ramdhana, Rais Abin; Syarfi, Muhammad; Jismulatif, Jismulatif (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research was aimed to discover whether there is any effect of using Canva as teaching media on descriptive text writing ability of SMP YLPI seventh grade students. The researcher conducted an interview to observe how writing was taught in the school, what were the difficulties students and teachers were facing and how familiar are they with the use of media in teaching. From this interview, researcher noticed that the students have difficulties developing ideas and challenged when learning writing. Experimental research was used in this study. This research is classified as a quasi-experiment, where in conducting this research, the writer involved one group pre-test and post-test design without the use of control group. Sampling technique used in this research was non-probability sampling with purposive sampling technique which took 20 students of class VII¹ as the sample of this research from the entire population of 37 first year students. The data were collected through a written test which were performed during the pre-test and post-test stage where it showed improvement in students’ five indicators which are content, organization, vocabulary, grammar, and mechanical before and after treatment was given. The results showed that the mean score of one group experimental class in pre-test was 60,5 and was 66 in post-test. the improvement of mean score from pre-test to post-test was 5,5. This indicates that Canva improves the students’ writing ability. These findings suggest that Canva can be used as a reliable teaching media to teach writing and improves students learning outcomes.